Storying the Good Life: Selfhood and Morality Through the Biographical Narrative Storyline - Bernasconi, Oriana (Qualitative Sociology Review, 2015)
The connection between personal story and morality has been long enunciated, but remains under-researched. Combining moral and narrative theory, this article approaches this relation by introducing a line of narrative inquiry oriented towards the exploration of how ethical intentions with regard to the good life manifest in and shape the biographical storyline and the self narratively assembled. The analysis encompasses a first case-based stage focused on the examination of the main motive of the personal story and its effects upon the organization of both self and narrative, followed by a comparative phase in which storylines and moral motives that work as reference of a set of biographical accounts belonging to different social positions, temporalities, or geographies are contrasted in order to establish linkages, breaks, and transformations in the relation between identity and morality across cases. This line of inquiry is applied into a research about intergenerational changes and continuities in the relation between selfhood and morality, based on life stories conducted with Chilean people of successive generations. In the conclusions, this strategy of narrative analysis is assessed in the light of current development of this field of qualitative social research.